Efek Atribut Chatbots Pada Hubungan Pelanggan Dengan Merek: PLS-SEM dan Analisis Peta Kepentingan-Kinerja Terhadap E-Commerce Shopee dan Tokopedia di Jakarta - Hutomo, Kayla Nirandra Alifia; Sugama, Nuresa Ibnu; Carolina, Elisabeth Christine; Riorini, Sri Vandayuli (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the effect that customer satisfaction gained from interaction with a chatbot can have on improving and empowering the overall quality of brand relationships. Therefore, this study will discuss about "The effects of chatbots attributes on customer relationships with brands: PLS-SEM and importance-performance map analysis of E-Commerce in Indonesia". This study uses hypothesis testing because it consists of 5 variables namely Information quality, System quality, Experience with chatbot, Customer satisfaction, and Brand relationship-quality. This research provides a deeper understanding of how the attributes of chatbots affect customer relationships with brands. It can be seen that customers are very happy to use chatbots and find the use of chatbots interesting.